Arabic Teaching and Learning in Matriculation Program for Al-Azhar Student’s Candidate - Zaki Ghufron; Endang Saeful Anwar; Azizah Alawiyah; Mufrodi Mufrodi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
This study aims to analyze Arabic learning material conducted by Pusiba and El-Darosah, which are official institutions for language studies for preparing prospective students who want to study in the Middle East, especially Egypt. This institution prepared language skills, aspects of mentality, and Islamic and national insight based on Al-Azhar's vision. This research was qualitative, using content analysis and sociolinguistic approaches, in which the study of a language was not only limited to the involvement of intrinsic as structure’s perceptions, but also extrinsic aspects, such as social, cultural, economic, political and others were done by post-structuralism. This research showed that the Pusiba and El-Darosah institutions as their official representatives have succeeded in explaining the identity of Al-Azhar, that is wasatiyah (moderate) Islamic views contained learning texts which were the main axis in learning Arabic such as al-Islam wa Huriyah al-‘Aqidah, al-‘Adl fi al-Islâm, al-‘Adl fi Mu’âmalah Ahl al-Diyânât al-Ukhrâ, Samâhah al-Islam ma’a Ahl al-Diyânât al-Ukhrâ, Mafhûm al-Huriyah fi al-Islam, al-Hiwâr ma’a al-Âkhar, and Al-Azhar wa Wasathiyah al-Islam, which were presented in several steps of Arabic learning books developed by Al-Azhar university.